Effectiveness of Community-Delivered Parent-Child Interaction Therapy Compared to Usual Care. Issue 4 (2nd October 2018) - Stokes, Jocelyn O.; Wallace, Nancy M.; McNeil, Cheryl B.
Abstract: This study used a quasi-experimental design to explore implementation of Parent-Child Interaction Therapy (PCIT) by community therapists after they completed their standard PCIT training. Child outcomes were compared to children in usual care. PCIT significantly differed from usual care in all aspects of treatment including that families in the PCIT group received significantly fewer hours of service. Children in PCIT had larger reductions in disruptive behavior. However, intent-to-treat analyses of child outcomes found no significant between-group differences. Limitations included cross contamination of participants between conditions and small sample size. More research is needed to examine the effectiveness of PCIT in the community, including its cost-effectiveness and long-term follow-up.